Analisis Pengaruh Kepadatan Penduduk dan Pendidikan Terhadap Inklusi Keuangan di Indonesia - Collyn, Daniel; Zalukhu, Rika Surianto; Hutauruk, Rapat Piter Sony; Sinaga, Murbanto (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2024)
The financial inclusion index of the Indonesian population has increased; however, there is a gap in financial inclusion and education between urban and rural areas. Therefore, this study aims to determine the influence of population density and education on financial inclusion in Indonesia, both partially and simultaneously. This research was conducted across 34 provinces in Indonesia. The study uses secondary data. The data used includes the financial inclusion index for 2022, obtained online from the Financial Services Authority (OJK) website at https://www.ojk.go.id/id/Default.aspx, as well as literacy rates and population density data for 2022, accessed online from the Central Statistics Agency (BPS) website at https://www.bps.go.id/id. The research data were then analyzed using multiple linear regression analysis methods. The analysis results show that population density has a positive and significant effect on financial inclusion in Indonesia. Meanwhile, education has a positive but not significant effect on financial inclusion in Indonesia. Population density and education simultaneously have a significant effect on financial inclusion in Indonesia. The results of this study imply that policies to enhance financial inclusion need to focus on the development of financial infrastructure in densely populated areas and adopt a comprehensive approach that involves more than just improving education.